VOCATIVE USE OF PEOPLE'S NAMES AND FAMILY RELATIONSHIPS IN SUNDANESE CONVERSATION IN THREE INTERNET SITES IN 2022 - Wahya Wahya (Lembaga Penelitian Universitas Pasundan, 2022)
Sundanese is a local language spoken by ethnic Sundanese Indonesian. Like any other language in the world, Sundanese also has language devices called vocatives to call addresses by speakers in a conversation. This paper explains the vocative, including the forms, which are the level of speech to show the social relations between speakers and addresses. The method used to collect the data is an observation method. The data analysis used is a distributional method with a sociolinguistic approach. From twenty-six data, there are sixteen people-name vocatives and ten family-relation vocatives. Of the sixteen people-name vocatives, six vocatives are in full-nickname form, namely Giri (1), Gilang (1), Lia (3), and Ani (1); and ten vocatives are in partial-nickname form, namely Lang (2) Nit (2), Tir (4), and Put (4). Meanwhile, ten family-relation vocatives consist of nine partial Sundanese-honorific forms, namely Kang (6), Neng (2), and Ceu (1), and one complete Sundanese-honorific form, namely Si Aa. Furthermore, from sixteen people-name vocatives, thirteen vocatives are used to show respect to others and three others to show familiar code. Meanwhile, all the family-relation vocatives are used to respect others. Hence, people-name vocatives are used to maintain social relationships on friendships. Meanwhile, family-relation vocatives are used to create new friendships.